2015
DOI: 10.1037/a0033955
|View full text |Cite
|
Sign up to set email alerts
|

Do self-control depletion and negative emotion contribute to intimate partner aggression? A lab-based study.

Abstract: Objective: Intimate partner aggression (IPA) is a serious problem among dating couples. The present study examined dyadic and situational processes that may lead to IPA perpetration among a sample of 59 heterosexual couples (total n = 118), within the framework of Finkel’s I3 model. Method: IPA was assessed using an in vivo aggression task, in the context of a weak inhibiting factor (self-control depletion) and a strong impellance factor (negative emotion) generated during in vivo verbal conflict between partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
4
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 67 publications
2
46
4
3
Order By: Relevance
“…In support of the CN model, several experimental studies have demonstrated a positive relationship between negative affect and aggression (Pedersen, 2006;Verona & Curtin, 2006). In addition, increases in negative emotion during couple conflict are positively related to IPA perpetration as measured with an analogue aggression task (Watkins, DiLillo, Hoffman, & Templin, 2013).…”
Section: Emotion Emotion Regulatory Strategies and Ipamentioning
confidence: 89%
See 4 more Smart Citations
“…In support of the CN model, several experimental studies have demonstrated a positive relationship between negative affect and aggression (Pedersen, 2006;Verona & Curtin, 2006). In addition, increases in negative emotion during couple conflict are positively related to IPA perpetration as measured with an analogue aggression task (Watkins, DiLillo, Hoffman, & Templin, 2013).…”
Section: Emotion Emotion Regulatory Strategies and Ipamentioning
confidence: 89%
“…Participants were randomized individually to an alcohol condition, and then mirroring procedures used by Ray et al (2008), asked to recall a past angering event with their partner using a randomly assigned emotion regulation strategy. In vivo partner aggression was assessed using a competitive reaction time game (Bushman 1995;Taylor, 1967;Watkins et al, 2013), in which participants were able to allocate a self-selected duration and volume of white noise, ostensibly to be heard by their intimate partner.…”
Section: Chapter 2: Methods Overall Designmentioning
confidence: 99%
See 3 more Smart Citations